Optimization of Ulva sp. Decomposition using H2SO4 with Microwave-Assisted Hydrolysis Method as Feedstock of Bioethanol - Palupi, Bekti; Rizalluddin, Muhammad; Septianti, Kiki; Rahmawati, Istiqomah; Fachri, Boy Arief; Rizkiana, Meta Fitri; Amini, Helda Wika (Universitas PGRI Madiun, 2023)
Bioethanol is a renewable energy used to reduce dependence on fossil fuels, which have negative impacts on the environment. Furthermore, Ulva sp. contains high levels of carbohydrates, making it potentially suitable as a raw material for bioethanol production. Therefore, this study aims to determine the optimal decomposition process using the microwave-assisted hydrolysis method with an acid solvent (H2SO4), by examining the effects of acid concentration, hydrolysis time, and microwave power. Optimization was carried out using several parameters such as hydrolysis time, microwave power, and the ratio of raw materials to solvents. The ANOVA test results showed that the hydrolysis variable parameter had a significant effect on the reducing sugar content obtained, evidenced by the R2 value of 0.9892. The highest reducing sugar content of 19.71 mg/mL was produced under the operating conditions of 15 min hydrolysis time, 450 W microwave power, and 0.065 g/mL ratio of raw material to solvents.